2015
DOI: 10.1175/jtech-d-14-00054.1
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of SAPHIR Calibration Using Quality Tropical Soundings

Abstract: The Sondeur Atmosphérique du Profil d'Humidité Intertropicale par Radiométrie (SAPHIR) instrument on board the Megha-Tropiques (MT) platform is a cross-track, multichannel microwave humidity sounder with six channels near the 183.31-GHz water vapor absorption line, a maximum scan angle of 42.968 (resulting in a maximum incidence angle of 50.78), a 1700-km-wide swath, and a footprint resolution of 10 km at nadir. SAPHIR L1A2 brightness temperature (BT) observations have been compared to BTs simulated by the rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 60 publications
(70 reference statements)
3
27
0
Order By: Relevance
“…For instance John and Buehler (2004) found that absorption by O 3 leads to a decrease of up to 0.5 K in the 183 ± 1 GHz channel of MHS using ARTS, with even smaller values for the other channels. Additional sensitivity tests performed by Clain et al (2015) using MonoRTM showed that the impact is also marginal in the 183.31 ± 11 GHz channel of SAPHIR (0.05 K on average). The details of how the molecular absorption is modeled may vary between different models, but the overall absorption is most commonly calculated for both the contribution near the line centers and the smoothly varying continuum.…”
Section: Spectroscopy Statusmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance John and Buehler (2004) found that absorption by O 3 leads to a decrease of up to 0.5 K in the 183 ± 1 GHz channel of MHS using ARTS, with even smaller values for the other channels. Additional sensitivity tests performed by Clain et al (2015) using MonoRTM showed that the impact is also marginal in the 183.31 ± 11 GHz channel of SAPHIR (0.05 K on average). The details of how the molecular absorption is modeled may vary between different models, but the overall absorption is most commonly calculated for both the contribution near the line centers and the smoothly varying continuum.…”
Section: Spectroscopy Statusmentioning
confidence: 99%
“…More recently, Chen et al (2010) have shown that, on a sample of diverse atmospheric profiles, fast and line-by-line RTMs agree within 0.1 K for MHS channels, and that this result was highly stable under humid conditions. In their evaluation of SAPHIR using RAOBs, Clain et al (2015) have shown that the three RTMs, RT-TOV.v10, ARTS and MonoRTM (Monochromatic Radiative Transfer Model; Clough et al, 2005;Payne et al, 2011), provide fairly consistent BTs on a common set of tropical profiles, the differences being in the range −1.50 K / 0.78 K, with the largest differences observed for the central channel (183 ± 0.2 GHz). These three RTMs rely on the currently most widely accepted model MT_CKD (MlawerTobin_CloughKneisysDavies;Mlawer et al, 2012) for the parametrization of the absorption due to the water vapor continuum.…”
Section: Behavior Of Radiative Transfer Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Ciesielski et al 2014). Here, we use the RS92 selected by Clain et al (2015) These two sets have been already explored for the evaluation of the upper-tropospheric humidity products derived from SAPHIR , and here we use the entire profiles. The cumulative distribution functions of the RH of these two sets are presented in Fig.…”
Section: ) Field Campaigns Measurementsmentioning
confidence: 99%
“…10%; « 1 5 60:03 3 RH for RH , 10%); and 2) a ground-check calibration uncertainty term « 2 different between day (« 2 5 60:05 3 RH 1 0:5) and night (« 2 5 60:04 3 RH 1 0:5). As discussed in Clain et al (2015) and following Immler et al (2010), these individual uncertainties can be reasonably considered as random and independent, and thus sum up for a total measurement uncertainty at a given point as « i 5 ffiffiffiffiffiffiffiffiffiffiffiffiffiffi ffi « …”
Section: Evaluation Using Radiosonde Profiles: Propagation Of Uncementioning
confidence: 99%